Modos de aplicação e distribuição de fósforo no solo e a resposta das culturas do trigo e feijoeiro - Merten, Gean Marcos (2020)
Phosphorus is found in a variety of metabolic processes in plants, such as in photosynthesis, respiration, gene transfers and processes which involve energy transfer, being indispensable for a good development of cultures and to reach the maximum potential, so the method of application of this nutrient can be a way for productivity gains according to each culture. The objective of this study was to evaluate the performance of wheat and common bean crops under different modes of application of phosphate fertilizer, as well as to evaluate the distribution of phosphorus at a depth of 0 – 20cm, in three modes of application of fertilizer in the two cultures in Red Latosol Dystrophic, with high phosphorus content. For the cultures, a randomized block design was used, with treatments consisting of three modes of application of phosphate fertilizer (100% applied to the haul, 100% applied to the sowing line and 50% applied to the haul and 50% to the sowing line), with five repetitions. Triple superphosphate (41% P2O5) was used as a phosphorus source, applying the doses of 115 and 250 kg ha-1 of the fertilizer in the wheat and bean crops respectively and according to the export of nutrients from the crops. For the soil, a randomized block design was used in a split plot layout, with the being the application method the plot, local factor (lines and between lines) the sub-plot and the sampling depth (0 – 5, 5 – 10, 10 – 15, 15 – 20 cm) the sub-subplot, with collections being made at seven points of each plot in the two wheat and bean crops in succession. At the time of wheat harvest, yield components were evaluated, for wheat, plant height, mass of a thousand grains and productivity were measured, and for beans, number of pods per plant, mass of a thousand grains and productivity. The first soil collection was carried out after the wheat harvest, with soil sampling being performed to quantify the levels of phosphorus added to the soil. The soil samples were collected at seven points per plot, four between the lines and three in the sowing lines, in a straight line in each plot, the same procedure was performed after the cultivation of beans. The modes of application of phosphorus did not increase the yield components of the cultures. The highest levels of phosphorus were observed in the superficial layer of the soil 0 – 5cm, but without effect of the application modes, so the application can be carried out both in the sowing furrow and when it is found in the soil high phosphorus content.